A novel high-voltage fault-tolerant permanent magnet synchronous generator for far offshore wind turbines - Pengzhao Wang; Xiangjun Zeng; Yiping Luo (International Journal of Electrical Power & Energy Systems)
Cost-effective and highly reliable wind generator systems are crucial for reducing the levelized cost of energy of far offshore wind farms. However, conventional three-phase wind generators with low output voltages necessitate complex power conversions and expensive offshore converter stations. This study proposes a novel high-voltage fault-tolerant permanent magnet synchronous generator (HVFTPMSG) to address this issue. Benefiting from a specially designed high-voltage coil and modular stator, the HVFTPMSG elevates the output voltage to approach HVDC transmission levels and exhibits excellent magnetic isolation performance. This work highlights the key design considerations of the HVFTPMSG and elaborates on its design and optimization methods using a 10 MW HVFTPMSG design example. A multiphysics coupling numerical model is developed to comprehensively evaluate the electromagnetic characteristics, thermal distribution, and electric field strength distribution of the design example. The design example optimized by the NSGA-III algorithm is compared with conventional generators of the same power rating regarding mass, cost, and efficiency. Furthermore, a scaled-down high-voltage coil prototype is developed to validate its insulation performance. The results indicate that the proposed HVFTPMSG is expected to be a competitive candidate for far offshore wind power applications.